Relevansi Rusia dan Turki Pada Konflik Armenia-Azerbaijan di Wilayah Nagorno-Karabakh - Tio Ari Pratama; Michael Ahmad Zulha; Gili Argenti (Peneliti.net, 2023)
This paper aims to reveal the national interests of foreign countries in the Armenian-Azerbaijan conflict in the Nagorno-Karabakh region. The Nagorno-Karabakh conflict began with the Armenian and Azeri ethnic conflict in the Soviet Union era, which has experienced a long cycle of conflict until now. The national interests of Russia and Turkey are interests in the political, military, and security fields that are mutually beneficial to both. The author finds the relevance of Russia and Turkey in this case. Russia maintains a presence in Armenia and disputed territorial borders and maintains control over the Caucasus region. Russia's role as a mediator makes its status as a world big country capable of handling phenomenal cases high. Turkey puts forward the supply of advanced weapons to Azerbaijan as the victor in the 2020 War, which Turkey considers a form of progress in producing military technology and being able to compete with other big countries. The political closeness between Russia-Armenia and between Turkey-Azerbaijan answers that national interests can be realized. The author uses a descriptive-qualitative method with literature studies derived from study books, journals, and trusted websites.